Experimental use of fuzzy logic in the maximum power point of photovoltaic module converters - Roberto F. Farfán; Carlos A. Cadena; Luis T. Villa (Revista Iberoamericana de Automática e Informática Industrial RIAI)
In this paper a fuzzy control expert system (FLC) is presented. Such system is developed for finding the maximum power point in photovoltaic modules. FLCs are widely used in various control systems, due to a suitable design which combines speed and accuracy in control. In the paper the input variables as well as the set of rules to be used in the control are defined. In such sense a photovoltaic module model - dcdc converter was validated in order to perform different simulations, to observe photovoltaic power variations in different operating points. The simulations show that the proposed control is suitable and better than a conventional system. Experimental measures indicate that the response of FLC developed under different conditions for irradiance and temperature are correct. The final physical implementation of FLC proposed is performed through a 32-bit PIC microcontroller.